Surgical options for patients with early-stage breast cancer and pathogenic germline variants: an oncologist perspectives - Abdel-Razeq, Hikmat (Frontiers in Oncology, 2023)
Breast cancer continues to be the most common cancer diagnosed among women worldwide. Family history of breast cancer is frequently encountered, and 5-15% of patients may carry inherited pathogenic germline variants, identification of which can be helpful for both; patients themselves and their unaffected close relatives. The availability and affordability of molecular diagnostics, like next generation sequencing (NGS), had resulted in wider adoption of such technologies to detect pathogenic variants of cancer-predisposing genes. International guidelines had recently broadened the indications for germline genetic testing to include much more patients, and also expanded the testing to include multi-gene panels, while some professional societies are calling for universal testing of all newly diagnosed patients with breast cancer, regardless of their age, personal or family history. The risk of experiencing a contralateral breast cancer (CBC) or ipsilateral recurrence, is well known. Such risk is highest with variants like BRCA1 and BRCA2, but less well-studied with other less common variants. The optimal local therapy for women with BRCA-associated breast cancer remains controversial but tends to be aggressive and may involve bilateral mastectomies, which may not have any survival advantage. Additionally, surgical management of unaffected women, known to carry a pathogenic cancer-predisposing gene, may vary from surveillance to bilateral mastectomies, too. The oncological safety, and the higher satisfaction of unaffected women and patients with new surgical techniques, like the skin-sparing (SSM) and nipple-sparing (NSM) mastectomies, eased up the process of counselling. In this review, we address the oncological safety of less aggressive surgical options for both, patients and unaffected carriers.